The bishop's wife - Harrison, Mette Ivie, 1970- (Harrison, Mette Ivie, 1970- Linda Wallheim mystery, 2014)
"In the predominantly Mormon city of Draper, Utah, some seemingly perfect families have deadly secrets...Linda Wallheim is the mother of five grown boys and the wife of a Mormon bishop. As bishop, Kurt Wallheim is the ward's designated spiritual father, and that makes Linda the ward's unofficial mother, and her days are filled with comfort visits, community service, and informal counseling. But Linda is increasingly troubled by the church's patriarchal structure and secrecy, especially as a disturbing situation takes shape in the ward."--